Understanding Affections in the Theology of Jonathan Edwards: The High Exercises of Divine Love - Huggins, Johnathan (Stellenbosch Theological Journal, 2021)
In this published form of his doctoral dissertation, Ryan Martin addresses the theme of affections in Jonathan Edwards's theology. Primarily, he aims to correct some common misunderstandings of Edwards's "affective psychology" that are present in some interpretations of Edwards's work.